1996
DOI: 10.1016/0926-6410(95)00033-x
|View full text |Cite
|
Sign up to set email alerts
|

Do imagined and executed actions share the same neural substrate?

Abstract: This paper addresses the issue of the functional correlates of motor imagery, using mental chronometry, monitoring the autonomic responses and measuring cerebral blood flow in humans. The timing of mentally simulated actions closely mimic actual movement times. Autonomic responses during motor imagery parallel the autonomic responses to actual exercise. Cerebral blood flow increases are observed in the motor cortices involved in the programming of actual movement (i.e. premotor cortex, anterior cingulate, infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
296
3
30

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 541 publications
(344 citation statements)
references
References 54 publications
15
296
3
30
Order By: Relevance
“…It has been suggested that kinesthetic motor imagery involves the same neural network as motor planning (Jeannerod, 1994;Jeannerod and Frak, 1999), which in turn is thought to rely on the same motor structures as motor execution (Johnson-Frey, 2004;Munzert et al, 2009;Sharma et al, 2006). In support of this view, motor imagery shares a number of similarities with overt movement execution, such as behavioral (Decety and Jeannerod, 1995) and physiological parameters (Kranczioch et al, 2008(Kranczioch et al, , 2009, and, importantly, the functional neuroanatomical correlates (Decety, 1996;Lotze and Halsband, 2006;Porro et al, 1996;Szameitat et al, 2007aSzameitat et al, , 2007b. In line with these findings, mental practice, i.e.…”
Section: Introductionmentioning
confidence: 78%
“…It has been suggested that kinesthetic motor imagery involves the same neural network as motor planning (Jeannerod, 1994;Jeannerod and Frak, 1999), which in turn is thought to rely on the same motor structures as motor execution (Johnson-Frey, 2004;Munzert et al, 2009;Sharma et al, 2006). In support of this view, motor imagery shares a number of similarities with overt movement execution, such as behavioral (Decety and Jeannerod, 1995) and physiological parameters (Kranczioch et al, 2008(Kranczioch et al, , 2009, and, importantly, the functional neuroanatomical correlates (Decety, 1996;Lotze and Halsband, 2006;Porro et al, 1996;Szameitat et al, 2007aSzameitat et al, , 2007b. In line with these findings, mental practice, i.e.…”
Section: Introductionmentioning
confidence: 78%
“…Others have reported even task-specific patterns of electromyographic activity with ISM [17,34]. Decety [6] used magnetic resonance spectroscopy (MRS) and found no evidence for biochemical activation in the target muscle during ISM. What would be an explanation for MI-activity in the absence of electromyographic activity?…”
Section: Discussionmentioning
confidence: 99%
“…However, a prominent feature of the studies mentioned above is the fact that regional cerebral activity was recorded during observation and/or mental simulation of actions, while we scanned volunteers during real production of large upper limb movements. Although considerable evidence supports the assumption that common mechanisms are involved in motor imagery and motor behaviour [e.g., Cochin et al, 1999;Decety, 1996;Decety et al, 1994;Parsons, 1994;Sirigu et al, 1996;Stephan et al, 1995], this is not true in all cases and functional differences may be found at the neuroanatomical level Gerardin et al, 2000]. A recent meta-analysis of the literature clearly showed that despite a generally good overlap between action execution, simulation, and observation, each of these target processes additionally recruits specific brain areas [Grèzes and Decety, 2001].…”
Section: A Dedicated Route For Novel Gestures Imitation Through Humanmentioning
confidence: 99%